Approach for evaluating instantaneous impact forces during submarine slide-pipeline interaction considering the inertial action. (1st February 2022) - Fan, Ning; Jiang, Jianxiong; Dong, Youkou; Guo, Lin; Song, Laifu
Abstract: With the rapid development of offshore oil and gas exploitation, submarine pipelines have become a common way to transport resources from the subsea wellhead to the production ship and the plant on shore. However, frequent submarine slide hazards pose a serious threat to the safe operation of the pipeline networks, in particular for the pipelines that have to pass through hazardous geological environments. Focusing on the instantaneous impact process of submarine slides on pipelines and the effects of the slide mass-related or pipeline-related parameters, this study includes a series of numerical simulations on the submarine slide-pipeline interaction at Reynolds numbers ranging from 0.36 to 287 via a computational fluid dynamics (CFD) method. The formation mechanism of the instantaneous impact forces is illuminated according to the characteristic analysis of the flow velocity and acceleration field around a pipeline during the slide-pipeline interaction. The conventional hybrid geotechnical-fluid dynamics framework describing the slide-pipeline forces is enhanced by considering the effect of inertial action, and force coefficients of different terms in the framework are quantified according to the CFD results data. Finally, an approach and detailed calculation table for evaluating the instantaneous impact forces are provided and verified by comparison with the previous experiments. Highlights: Formation mechanism of the instantaneous impact forces caused by slide mass is revealed by the analysis of flow velocity and acceleration variation. The hybrid geotechnical-fluid dynamics framework for slide-pipeline interactions is developed by considering the acceleration-induced inertial action. An approach for evaluating the peak slide-pipeline interaction forces is provided based on the hybrid framework developed. A calculation table containing the complete evaluation process on the impact forces caused by submarine slides is recommended to facilitate the application of the presented approach.